Legal obligations of halal producers; characterization & evaluation = "الإلتزامات القانونية لمنتجي المنتجات الحلال "توصيف وتقييم - Ahmed, Ahmed Salem; Laeba, Muhammad (Universiti Sultan Zainal Abidin (UNiSZA), 2018)
The producer is the secret of the product's existence. However, the Halal standards have not paid much attention to his side, particularly in terms of his legal obligations, which are the basis of work in the Halal sector. The producer here means who processes the production, as well as all the logistics operators; starting from the manufacturers, suppliers, marketers, transporters etc., whom the researcher wills to explain their obligations according to the Malaysian standards of Halal products as it is the most important standards in this regard. In addition to an attempt to assess those standards in terms of their applicability, and the efficiency of the legislative policy followed in making them in terms of absorption the general frameworks, in order to strengthen their legal positions, and to contribute to the strengthening of the halal products' legal framework in general. Through adoption of descriptive and analytical methods in the research, it is found that the Malaysian standards established an acceptable basis for the legal obligations of producers. However, there are some shortcomings in the difficulty of meeting some legal and technical obligations, and their cumbersome in compliance with the systems, especially in the double-activity producers to produce halal and non-halal products. The research recommends re-enactment of the policy adopted in these obligations to be more realistic and comprehensive, as well as separation between the producers of halal and non-halal products to facilitate compliance in one side, and to ensure production Halal on the other hand, and opening new investment prospect for emerging companies or existing dual companies to dedicate all its research and technical efforts for the Halal industry. ********************************************************* ن ً ذكر خصوصا ُ ي ٍ إىتمام ُ ه ُ عتَُ وعلى الرغم من ذلك فإن معايتَ الحلال لم ت ،جَ نت ُ وجود الد ّ ج ىو سر ِ نت ُ الد ، ج من قام بعملية الإنتاج َ نت ُ ونعتٍ بالد ، ع الحلال عتبر أساس العمل في قطا ُ حيث إلتزاماتو القانونية التي ت وكذلك كافة القائمتُ على الخدمات اللوجستية من ُ مصنعتُ وموردين ومسوقتُ وناقلتُ وغتَىم، وىو ما للمعايتَ الداليزية للمنتجات الحلال لكونها من أىم ً أستشعر معو الباحث بيان تلك الإلتزامات وفقا الدعايتَ في ىذا الشأن، بالإضافة إلى لزاولة تقييم تلك الإلتزامات من حيث مدى قابليتها للتطبيق، ومدى كفاءة السياسة التشريعية ة بعة في تقنينها من حيث إستيعابها للأطر القانونية السائد َّ ت ُ لمحاولة ، الد ، عام ٍ وللمساهمة في تعزيز الإطار القانوني للمنتجات الحلال بشكل ومن خلال ، تعزيز مراكزىم القانونية البحث بإنتهاج الدنهجتُ الوصفي والتحليلي تبتُ أن الدواصفات القياسية الداليزية قد أرست أساس ً ا ً مقبول إل أنو تعتًيو بعض العيوب الدتمثلة في صعوبة الوفاء ببعض الإلتزامات من ،للإلتزامات القانونية للمنتجتُ ،النواحي القانونية والفنية ُ ب الإلتزامات بشكل ي ُّ وتشع رىق نظم الإمتثال في ً خصوصا ، في متابعتها ُ الدنتجتُ مزدوجي النشاط لإنتاج الدنتجات الحلال وغتَ الحلال، وىو ما أوصى معو الباحث بضرورة إعادة السياسة التشريعة الدتبعة في ىذه الإلتزامات بحيث تكون أكثر واقعية وشمولية، عن الفصل ً فضلا وضمان ، بتُ منتجي الدنتجات الحلال وغتَ الحلال بشكل نهائي لتسهيل عملية الإمتثال من ناحية الح ى أخر ٍ بالإضافة إلى فتح آفاق إستثمارية جديدة لشركات ناشئة، أو ، لال في الدنتجات من ناحية للشركات القائمة الدزدوجة ل. كافة لرهوداتها البحثية والتقنية لصناعة الحلال سِّ كر ُ ت